Factors influencing 14C concentrations of algal and archaeal lipids and their associated sea surface temperature proxies in the Black Sea. (1st September 2016) - Kusch, Stephanie; Rethemeyer, Janet; Hopmans, Ellen C.; Wacker, Lukas; Mollenhauer, Gesine
Abstract: Understanding the preservation and deposition history of organic molecules is crucial for the understanding of paleoenvironmental information contained in their abundance ratios such as U k′ 37 and TEX86 used as proxies for sea surface temperature (SST). Based on their relatively high refractivity, alkenones and glycerol dialkyl glycerol tetraethers (GDGTs) can survive postdepositional processes like lateral transport, potentially causing inferred SSTs to be misleading. Likewise, selective preservation of alkenones and GDGTs may cause biases of the SST proxies themselves and can lead to decoupling of both proxy records . Here we report compound-specific radiocarbon data of marine biomarkers including alkenones, GDGTs, and low molecular weight (LMW) n -fatty acids from Black Sea sediments deposited under different redox regimes to evaluate the potentially differential preservation of both biomarker classes and its effect on the SST indices U k′ 37 and TEX86 . The decadal Δ 14 C values of alkenones, GDGTs, and LMW n -fatty acids indicate similar preservation under oxic, suboxic, and anoxic redox regimes and no contribution of pre-aged compounds, e.g., by lateral supply. Moreover, similar 14 C concentrations of crenarchaeol, alkenones, and LMW n -fatty acids imply that the thaumarchaeotal GDGTs preserved in these sediments are produced in the euphotic zone rather than in subsurface/thermocline waters. However, we observe biomarker-based SSTs that strongly deviate (ΔSST up to 8.4 °C) from in situ measured mean annual SSTs in the Black Sea. This is not due to redox-dependent differential biomarker preservation as implied by their Δ 14 C values and spatial SST pattern. Since contributions from different sources can largely be excluded, the deviation of the U k′ 37 and TEX86 proxy-derived SSTs from in situ SSTs requires further study of phylogenetic and other yet unknown environmental controls on alkenone and GDGT lipid distributions in the Black Sea.